Fear of Missing Out among Adolescent: A Narrative Study on Self-Esteem, Social Interaction, and Social Anxiety - Saputra, Al Aziz; Sujadi, Eko (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2025)
Fear of Missing Out (FoMO) is a feeling of anxiety or fear of being left behind when others undergo valuable experiences that one does not. Based on Solution Focused Brief Counseling (SFBC) theory, FoMO arises due to the inability of individuals to manage thoughts and feelings, resulting in problematic behavior. This study aims to understand the emotional dynamics and social interactions of adolescents who experience FoMO, focusing on three main indicators: self-esteem, social interaction, and social anxiety. The study used a qualitative narrative approach, with three adolescents from several villages in Kerinci Regency, Jambi, as informants. Data were collected through in-depth interviews and analyzed using thematic analysis techniques. The results showed that FoMO affects adolescents' emotional state and social interactions, particularly in triggering anxiety, worry, and low self-esteem. Adolescents' responses to FoMO vary, depending on their level of ability to manage social pressure. These findings provide important implications for Guidance and Counseling (BK) practitioners in providing emotional mentoring services, self-esteem strengthening training, and education on the healthy use of social media. In addition, BK also plays a role in introducing coping techniques and social comparison reduction strategies to support adolescents' psychosocial well-being.